Sex Differences in Associations between Early Adversity, Child Temperament, and Behavior Problems - Coe, Jesse L. (Int J Behav Dev, 2020)
Early adversity is associated with both internalizing and externalizing problems among children, and effects of adversity on dimensions of child temperament may underlie these links. However, very little is known about the role of child sex in these processes. The current study examined if there are indirect effects of early adversity on behavior problems through dimensions of child temperament and if these indirect effects vary across child sex. Participants in this multimethod (parent-report survey, semi-structured interview, child protection records) study included 274 preschool-aged children (M(age) = 50.86 months; 52% with documented case of moderate-severe maltreatment) and their primary caregivers assessed at two time-points spaced 6 months apart. Results of multi-group path analyses revealed that while anger mediated associations between lifetime stress and behavior problems for the full sample, inhibitory control and appropriate attentional allocation were significant intermediary mechanisms of lifetime stress for boys, but not for girls. Inhibitory control mediated associations between maltreatment and behavior problems for the full sample, but appropriate attentional allocation mediated these associations for boys only. Results suggest that early adversity influences child behavior problems through child temperament, particularly for boys. This work supports the perspective that temperament is influenced by characteristics of the early rearing environment, and the indirect effects of adversity on behavior problems through temperament vary across sex.